(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The study is dedicated to exploring the essence of accounting policy of an enterprise and analyzing the influence of internal and external factors on its formation and practical application. Accounting policy plays a crucial role for economic entities, as it determines the proper organization of accounting based on which financial statements are prepared and managerial decisions are made. It is the accounting policy that structures information and establishes a set of actions for the accounting representation of business processes. The structure of accounting policy, in turn, depends on the type of activities of the economic entity, production or trading technologies, organizational status, and size. The study examines internal factors such as organizational and legal form, scale of operations, production and organizational structure, information provision, personnel qualifications, and other aspects of internal enterprise activities that influence accounting policy. External factors are also analyzed, including regulatory and legal regulations, industry-specific considerations, taxation system, market infrastructure, and other external conditions that significantly impact the formation and practice of accounting policy. A comprehensive approach to the formation of accounting policy, which involves analyzing internal and external factors, enables the development of an effective strategy to achieve set objectives and adapt accounting policy to changes in the internal and external environment. Considering all relevant factors and properly shaping accounting policy will contribute to optimal accounting management, control over financial resources, and timely managerial decision-making within the enterprise. The main objective of the research is to identify various approaches to defining accounting policy proposed by authors from different sources and to analyze the impact of factors on the formation of the enterprise’s accounting policy. The research holds practical significance for enterprises aiming to enhance the effectiveness of their accounting policy and adapt to changes in the internal and external environment. It is also relevant for researchers and students exploring issues related to accounting and enterprise management.